Homoeopathy in Cancer Pain Palliation and End of Life with Future Perspectives - Sachdeva, Jyoti; Dey, Joy Kumar (Homœopathic Links, 2019)
Pain is a common companion of people receiving palliative care in cancer and at the end of life. Cancer pain is multifactorial and complex. Its impact can be devastating, with increased morbidity and poor quality of life, if not treated adequately. Cancer pain management is a challenging task both due to disease process and due to treatment-related side effects; therefore, it requires a holistic approach which can be covered by homoeopathic remedies. The purpose of this article is to enlighten the scope and future perspective of homoeopathy in pain palliative care and at the end of life. This article summarises the need of multidimensional approach towards the cancer pain palliation and at the end of life in which homoeopathy may play a key role of supportive care. Homoeopathy may become a valuable treatment in palliative care to provide relief and comfort to the dying patient, and therefore the fear of death may reduce and the family may be better prepared for the bereavement. Homoeopathy can well integrate with standard oncologic cares to improve patient outcome including symptom burden, quality of life and end-of-life outcomes, all achieved with low associated costs.
Keywords: cancer pain; end of life; homoeopathy; palliation